Serratus Anterior Plane Block for Pain Management After Video-Assisted Thoracoscopic Surgeries: A Narrative Review - Shahab Ahmadzadeh; Macie A. Serio; Angela Nguyen; Drew R. Dethloff; Camille Robichaux; Chizoba N. Mosieri; Sahar Shekoohi; Alan D. Kaye (Medicina, 2025)
Video-assisted thoracoscopic surgery (VATS) is a minimally invasive diagnostic and therapeutic procedure utilized in various thoracic conditions. VATS has grown in popularity with ever-expanding knowledge of enhanced recovery after surgery (ERAS) protocols and its benefits regarding patient care and outcomes. Pain control following VATS is of utmost importance to minimize the complication risk. Options for pain control following VATS have traditionally included systemic IV analgesia but have evolved to include loco-regional analgesia as well. The serratus anterior plane block (SAPB) is one form of loco-regional analgesia utilized in VATS that has been shown to provide effective pain control of the anterolateral chest wall. Patients who received SAPB compared to control methods of anesthesia demonstrated significant decreases in postoperative pain and postoperative opioid consumption. SAPB is effective and offers a promising safety profile as the block is typically more superficial than other types of loco-regional analgesia. This review outlines the recent literature surrounding the use of SAPB for pain control in VATS.